5(3x-2)+12-6x=-43

Simple and best practice solution for 5(3x-2)+12-6x=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x-2)+12-6x=-43 equation:



5(3x-2)+12-6x=-43
We move all terms to the left:
5(3x-2)+12-6x-(-43)=0
We add all the numbers together, and all the variables
-6x+5(3x-2)+55=0
We multiply parentheses
-6x+15x-10+55=0
We add all the numbers together, and all the variables
9x+45=0
We move all terms containing x to the left, all other terms to the right
9x=-45
x=-45/9
x=-5

See similar equations:

| 5=x+4=8 | | 5(2x+8)^2=-80 | | 8x^+40x^2=O | | 3.5/h=-2 | | 5x+12x-2x=15-10 | | 3(3x+5)-12x-4=5 | | 12x+28x+15=0 | | -1x+6=x+14 | | 0.35x200=70 | | 5x+2=8x+4=15x-18 | | x2-7x-7=0 | | -1/4*7+3r=-1/8r | | 4x-7x+17=44 | | -1-(k-8)=23+k | | -3(6-10v-5v)=0 | | 4x-9=-3(x+8)-27 | | 2/3(-3x+9)=-2 | | x/13=3/5.79 | | -16x^2+185=0 | | 15/7=30/k | | -3(6-10v-5v=0 | | P2-7p-7=0 | | -8-8(-4-2n)=0 | | 2(1x+5)=16 | | 3a-(3-(5a-11))=30 | | 9(x-6)+1=4x-3 | | 5x-2(x+2)=11-(2x+5) | | 15a-2*4a+5=-6a | | 4m-(3m-(m+1))+6m=9 | | 21x+25+675x-27/3=180 | | 15(x+7)-12=48 | | 2n+4+66=70 |

Equations solver categories